2021
DOI: 10.3390/w13091265
|View full text |Cite
|
Sign up to set email alerts
|

Applicability Study of Hydrological Period Identification Methods: Application to Huayuankou and Lijin in the Yellow River Basin, China

Abstract: Identifying implicit periodicities in hydrological data is significant for managing river–basin water resources and establishing flood forecasting systems. However, the complexity and randomness of hydrological systems make it difficult to detect hidden oscillatory characteristics. This study discusses the performance and applicability of five period identification methods, namely periodograms, autocorrelation analysis (AA), maximum entropy spectral analysis (MESA), wavelet analysis (WA), and the Hilbert–Huang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…It has made very significant progress compared in the area of hydrology. The application in the hydrology field has shown its success since the beginning of the last decade, in particular in the hydrological time series analysis and forecasting (e.g., Chen et al 2021;Zhang et al 2021;Shi et al 2021;Saraiva et al 2021;Abda et al 2021;Freire et al 2019;Abda and Chettih 2018;Reddy and Adarsh 2016;Huang et al 2014;. It is worth highlighting that although CWT could give information and solution for our requirements, DWT and HHT are more flexible.…”
Section: New Insights From the Proposed Hybrid Methodsmentioning
confidence: 99%
“…It has made very significant progress compared in the area of hydrology. The application in the hydrology field has shown its success since the beginning of the last decade, in particular in the hydrological time series analysis and forecasting (e.g., Chen et al 2021;Zhang et al 2021;Shi et al 2021;Saraiva et al 2021;Abda et al 2021;Freire et al 2019;Abda and Chettih 2018;Reddy and Adarsh 2016;Huang et al 2014;. It is worth highlighting that although CWT could give information and solution for our requirements, DWT and HHT are more flexible.…”
Section: New Insights From the Proposed Hybrid Methodsmentioning
confidence: 99%
“…For example, Pham et al (2021) highlights that the main reason for data pre-processing is to eliminate possible noise in the time series data and, thus, avoid unwanted model training. Chen et al (2021) highlights that useful information hidden in the flow series can be extracted effectively through data pre-processing, thus improving prediction accuracy. Baydaroğlu et al (2018) found, that hybrid modeling of SSA with support vector regression (SVR), on monthly flow data from the Kızılırmak River in Turkey proved successful, yielding values of coefficient of determination (0.…”
Section: Series Reconstructionmentioning
confidence: 99%
“…The identification of periodicities in hydrological data is important for the management of water resources in hydrographic basins and for the establishment of flood forecasting systems. However, the complexity and randomness of hydrological systems make it difficult to detect hidden oscillatory features (Chen et al, 2021;Pham et al, 2021). Therefore, decomposition techniques, such as SSA, are important tools for helping watercourse hydrological behavior understanding.…”
Section: Series Reconstructionmentioning
confidence: 99%
“…A similar study was conducted by Roshani et al [9] who determined the existence of a certain water cycle of the Rudhan River (Iran), especially during the summer and autumn seasons. Some research used the same methodology to investigate the correlation between water level changes and climate changes [13], [14]. In order to determine the discharge cycles and their repetition, the first step include trend analysis and registration of changes of the hydrological parameter.…”
Section: Introductionmentioning
confidence: 99%